2013
DOI: 10.1016/j.taap.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The cytochrome P450 2AA gene cluster in zebrafish (Danio rerio): Expression of CYP2AA1 and CYP2AA2 and response to phenobarbital-type inducers

Abstract: The cytochrome P450 (CYP) 2 gene family is the largest and most diverse CYP gene family in vertebrates. In zebrafish, we have identified 10 genes in a new subfamily CYP2AA, which does not show orthology to any human or other mammalian CYP genes. Here we report evolutionary and structural relationships of the 10 CYP2AA genes and expression of the first two genes, CYP2AA1 and CYP2AA2. Parsimony reconstruction of the tandem duplication pattern for the CYP2AA cluster suggests that CYP2AA1, CYP2AA2 and CYP2AA3 like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…QPCR were run on a MyIQ single-color real-time thermocycler with IQ Sybr green Supermix from Bio-Rad. The E -ΔΔCt method was used for relative quantification (Livak and Schmittgen, 2001), using the geometric mean of aryl hydrocarbon receptor nuclear translocator 2 ( arnt2 ) and elongation factor 1 alpha ( ef1α ) Ct values for normalization (Kubota et al, 2013; Morrison et al, 2014). Primers were: 5’-TACAGGAGGTGGAAGGAAAGGTG-3’ (F) and 5’-GACGACCACCAAGGGCATAGATAAC-3’ (R) for CYP20A1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QPCR were run on a MyIQ single-color real-time thermocycler with IQ Sybr green Supermix from Bio-Rad. The E -ΔΔCt method was used for relative quantification (Livak and Schmittgen, 2001), using the geometric mean of aryl hydrocarbon receptor nuclear translocator 2 ( arnt2 ) and elongation factor 1 alpha ( ef1α ) Ct values for normalization (Kubota et al, 2013; Morrison et al, 2014). Primers were: 5’-TACAGGAGGTGGAAGGAAAGGTG-3’ (F) and 5’-GACGACCACCAAGGGCATAGATAAC-3’ (R) for CYP20A1 .…”
Section: Methodsmentioning
confidence: 99%
“…Functions can be inferred for many CYPs in gene families 5-51, based on activities of known mammalian orthologs, yet predicted function has been confirmed in few cases (e.g., the lanosterol 14α-demethylase CYP51) (Morrison et al, 2014). In gene families 1-3, there has been much lineage specific expansion, resulting in co-orthologs, most with unknown function (Kubota et al, 2013). Thus, many zebrafish CYPs still are properly considered orphans, including CYP20A1.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of biotransformation enzymes in mammals is mediated by three main transcription factors: the AHR, the PXR and the constitutive androstane receptor (CAR) (Köhle and Bock, 2009). Like the AHR, the PXR is a xenobiotic sensor responsible for a wide range of ligand-mediated activities, and induces genes such as CYP2s and CYP3s in both rodents and fish (Waxman, 1999;Bresolin et al, 2005;Bainy et al, 2013;Kubota et al, 2013). Phylogenetic analysis indicates that unlike mammalian models, zebrafish models do not contain Car , which highlights the potential key function of Pxr in zebrafsh.…”
Section: Discussionmentioning
confidence: 99%
“…However, this genomic locus share poor synteny with mammalian CYP2 genes3435, and the different Cyp2aa members may have distinct substrate specificities32. Previous studies have demonstrated that the Cyp2aas transform a broad range of xenobiotic substrates3536, whereas little is known regarding their physiological functions. Our study has identified physiological roles of Cyp2aa9 in HSCs formation during embryonic development.…”
Section: Discussionmentioning
confidence: 99%